2022
DOI: 10.1101/2022.10.14.512258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The tendon interfascicular basement membrane provides a vascular niche for CD146+pericyte cell subpopulations

Abstract: The interfascicular matrix (IFM) is critical to the mechanical adaptations and response to load in energy-storing tendons, such as the human Achilles and equine superficial digital flexor tendon (SDFT). We hypothesized that the IFM is a tendon progenitor cell niche housing an exclusive cell subpopulation. Immunolabelling of equine SDFT was used to identify the IFM niche, localising expression patterns of CD31 (endothelial cells), CD146 (IFM cells) and LAMA4 (IFM basement membrane marker). Magnetic-activated ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(85 reference statements)
1
1
0
Order By: Relevance
“…Our results demonstrate that the IFM houses a unique tenocyte population that can be distinguished from fascicular tenocytes due to higher expression of PRG4 and TNXB, and lower expression of COMP, LOX and THBS4. Tendon endothelial, mural and immune cell populations also localise to the IFM, supporting recent work that has identified the presence of an endothelial-like basement membrane in the IFM (Marr et al, 2022). Previous scRNAseq studies of mouse and human tendons have identified a range of similar cell populations to those identified in the current study, encompassing tenocytes, endothelial cells and immune cells (Kendal et al, 2020, De Micheli et al, 2020.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results demonstrate that the IFM houses a unique tenocyte population that can be distinguished from fascicular tenocytes due to higher expression of PRG4 and TNXB, and lower expression of COMP, LOX and THBS4. Tendon endothelial, mural and immune cell populations also localise to the IFM, supporting recent work that has identified the presence of an endothelial-like basement membrane in the IFM (Marr et al, 2022). Previous scRNAseq studies of mouse and human tendons have identified a range of similar cell populations to those identified in the current study, encompassing tenocytes, endothelial cells and immune cells (Kendal et al, 2020, De Micheli et al, 2020.…”
Section: Discussionsupporting
confidence: 88%
“…Results showed alterations in expression of matrisomal genes with ageing in tenocytes, with a general decrease in expression of collagens, with the exception of COL4A1&2 , which increased in IFM subclusters. These genes encode an integral component of the IFM basement membrane (Marr et al, 2022), and therefore these changes may result in alterations to IFM basement membrane structure. In addition, the decrease in LAMA4 expression with ageing in tenocytes may have important implications for healing, as it has previously been shown that LAMA4 may be important for the recruitment of IFM cell populations after injury (Marr et al, 2021).…”
Section: Discussionmentioning
confidence: 99%